Rameau's niece : a novel - Schine, Cathleen (Ticknor & Fields, 1993)
Margaret Nathan is the scholarly though mortifyingly forgetful author of The Anatomy of Madame de Montigny, an unlikely best seller celebrated by feminists and by deconstructionists, and soon to be a television movie. Happily married to a benevolently egotistical Columbia professor, Margaret seems blessed - until she finds herself seduced by the libertine novel she has discovered in the library. Thus begins a series of amorous contretemps that plunge Margaret into the maelstrom of contemporary sexual practice, until she is washed up panting on the farther shore of self-understanding.